2021
DOI: 10.1007/s11356-021-13778-w
|View full text |Cite
|
Sign up to set email alerts
|

Association between ambient air pollution and cause-specific mortality in Cape Town, Durban, and Johannesburg, South Africa: any susceptible groups?

Abstract: Studies have confirmed that adverse human health effects that are associated with exposure to air pollution may differ depending on other factors such as age, gender, environmental conditions, and socio-economic factors. This study was conducted to assess the association between ambient air pollution and cause-specific mortality in the three big cities in South Africa and to determine the susceptible groups thereof. Cause-specific mortality data for all ages and PM10, NO2, and SO2 in Cape Town, Durban, and Joh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…For instance, Orellano et al found a 0.91% (95% CI: 0.6-1.2%) increased risk for a 10 µg/m 3 rise in PM 10 , and Newell et al reported a corresponding estimate of 0.38% (95% CI: 0•33-0•43). Our results are also consistent with other findings from Cape Town Wichmann et al [7] and Thabethe et al [15] reported non-significant positive associations of PM 10 with daily RD mortality rates as well. The same studies also reported results similar to ours for SO 2 .…”
Section: Respiratory Diseasesupporting
confidence: 93%
See 1 more Smart Citation
“…For instance, Orellano et al found a 0.91% (95% CI: 0.6-1.2%) increased risk for a 10 µg/m 3 rise in PM 10 , and Newell et al reported a corresponding estimate of 0.38% (95% CI: 0•33-0•43). Our results are also consistent with other findings from Cape Town Wichmann et al [7] and Thabethe et al [15] reported non-significant positive associations of PM 10 with daily RD mortality rates as well. The same studies also reported results similar to ours for SO 2 .…”
Section: Respiratory Diseasesupporting
confidence: 93%
“…Air quality monitoring in other regions of the African continent is not well established, resulting in a lack of data for such studies. In the City of Cape Town, epidemiological time-series studies have shown shortterm associations between air pollution and cardio-respiratory disease mortality [7,15], however none of them assessed the independent effects of multiple pollutants. As people are exposed to multiple pollutants in the atmosphere-it is crucial to estimate the independent short-term effects of individual pollutants in multi-pollutant models by including the different pollutants simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…There have been a few studies to date in SA and SSA at large that have explored the short-term association between monitored air pollutants and any health outcomes [ 6 , 11 , 12 , 13 ], but none has quantified the joint health effects of multiple pollutants on hospital admissions for any health outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Much is known about the relation between high ambient temperature, air pollution, all-course and cardiovascular mortality [122], independent associations of hot weather, polluted air environment, and respiratory health [1,67,123], but the combined effect on disease-specific events, such as respiratory, is less clear. The current review shows the role of pollutants on respiratory health impacts may vary with hot weather conditions.…”
Section: Discussionmentioning
confidence: 99%